Raymond Williams’ Notion of Culture: A Life of Metis in the Perception of Louis Riel (International Journal of Food and Nutritional Sciences, 2022)
A standard approach to turn back to the history of Métis is genealogy-based methodology. It is a community in Canada known and recognised within the communities. The term itself opens the struggles and issues of the people. An argument on the identity of Métis is still questioned in the society, demanding the people to answer individually. However, the rights of law persist in the Canadian Constitution and it is unbothered. Unlike other countries, Canada has distinct peoples like First Nations, Métis, and Inuit as Indigenous or Aboriginal peoples. Métis feel that they do not have any true representation of themselves as they are treated with biased everywhere they go. This paper analyses the backdrop of social interactions and narrows down to the Métis and their community by retelling the history of the native.